Focusing of visual attention at rest and during physical exercise in soccer players - Pesce, C.; Tessitore, A.; Casella, R.; Pirritano, M.; Caprancia, L. (Journal of Sports Sciences, 2007)
In this study, we investigated the focus of visual attention in expert soccer players together with the effects of acute bouts of physical exercise on performance. In two discriminative reaction time experiments, which were performed both at rest and under submaximal physical workload, visual attention was cued by means of spatial cues of different size followed by compound stimuli with local and global target features. Soccer players were slower than non-athletes in reacting to local compared with global targets, but were faster in switching from local to global attending. Thus, soccer players appear to be less skilled in local attending, but better able than non-athletes to rapidly "zoom out" the focus of attention. Non-athletes generally showed faster performance under physical load, as expected according to the hypothesis of exercise-induced increases in arousal and/or activation and in resource allocation. In contrast, soccer players showed a more differentiated pattern of exercise-induced facilitation that selectively affects specific components of the attentional performance and is interpreted by referring to the role played by individual expertise and cognitive effort.